Ukrainian dance culture expression in phraseology (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
This article investigates semantic and ethnic cultural peculiarities of Ukrainian idioms and set expressions, which represent specific dance culture of our nation, describe the nature of expressive movements and provide information about non-verbal components of choreographic practice (posture, gestures etc.). Ukrainians’ dance abilities are determined as a unique and original phenomenon, verbally represented in phraseology units. The analysis involves the following groups of set expressions: 1) idioms with verbal “dance” component; 2) idioms with inner component structure which stands for moving activity similar to dance. This paper confirms that the semantics of set expressions in the first group contains metaphorical meaning becoming clear only through additional cultural commentary and symbol interpretation. The idioms of the second group illustrate non-verbal human activity and assess the body language. Their meaning makes it possible to identify Ukrainian mental traits through the prism of dance culture. This research also provides Russian set expressions to emphasize national expressiveness of cultural component in Ukrainian and Belarusian phraseology units, which have the same Eastern Slavic language background.Factual material observation manifests that the dance originates as a result of behavior and scenario ritualization. Idiomatic units become the way to express general need of regulating person’s dance moves on the biological basis as a means of transmitting cognitive adaptively valuable information. Dance language is deeply influenced and caused by social and cultural life. That is why studying of the wildlife, interpersonal communication, international relations, even military affairs contributes to forming certain models of dance culture. Non-linguistic information involved in the research turns to be the source of set expressions in phraseology. This paper illustrates that the set expressions of dance culture contain emotional and evaluative expressiveness and expressive means, mostly stylistically reduced, providing a humorous assessment of reality.
Keywords: dance; dance culture; idiom; ethnic culture; mental model; mental image; body language; hopak